2011
DOI: 10.1590/s1679-62252011005000038
|View full text |Cite
|
Sign up to set email alerts
|

Age, growth, and reproductive aspects of the dusky grouper Mycteroperca marginata (Actinopterygii: Epinephelidae) in a man-made rocky habitat in southern Brazil

Abstract: The dusky grouper, Mycteroperca marginata, is an important commercial marine fish that is currently considered an endangered species worldwide and listed as overexploited in Brazil. Although its reproductive biology has been studied elsewhere, no information is available for populations in its southernmost distribution limit on the Brazilian coast. The present work investigates age structure, growth and reproduction of individuals inhabiting a pair of rocky jetties, about 4.5 km long each, located in the mouth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 23 publications
1
10
0
4
Order By: Relevance
“…Other studies also found a high proportion of young individuals [20,35]. We agree with Condini et al [20] that spawning groupers should be located at deeper ranges; however, we also suggest that the hypothesis that spawning groupers could be located in rocky areas far from the shoreline can be very plausible [43]. Areas far from the shore or at greater depth ranges are sites that smallscale fishers usually cannot reach with their technologies (see fishing spots for groupers used by small-scale fisheries of Copacabana in [18].…”
Section: Discussionsupporting
confidence: 90%
“…Other studies also found a high proportion of young individuals [20,35]. We agree with Condini et al [20] that spawning groupers should be located at deeper ranges; however, we also suggest that the hypothesis that spawning groupers could be located in rocky areas far from the shoreline can be very plausible [43]. Areas far from the shore or at greater depth ranges are sites that smallscale fishers usually cannot reach with their technologies (see fishing spots for groupers used by small-scale fisheries of Copacabana in [18].…”
Section: Discussionsupporting
confidence: 90%
“…In contrast, only immature individuals and resting mature females are found along rocky substrate in the littoral zone (Seyboth et al 2011). Although comparative studies suggest that dusky grouper growth rates are higher in neritic habitats (Condini et al 2014b), the relative importance of the different habitats for this endangered species remains unknown.…”
Section: Dusky Grouper Epinephelus Marginatusmentioning
confidence: 99%
“…Specifically, the mean sizes at ages 3, 4, 5, 6, and 7 of fish collected offshore at the Carpinteiro Bank (depths of 15-25 m) were compared with the mean sizes of fish collected from the inshore rocky jetties of Rio Grande (depths <5 m) from 2007 to 2009 that were previously reported by Seyboth et al (2011). These age groups were selected on the basis of the simultaneous availability of 10 or more individuals per age group at both sites.…”
Section: Framework For Habitat Comparisonmentioning
confidence: 99%
“…Lengthat-age data of inshore dusky groupers were made available by those authors. Otoliths in this study and in Seyboth et al (2011) were read by the same person. Statistical analysis was conducted through a one-way analysis of variance after verification of the assumptions of normality and homoscedasticity (Zar, 1999).…”
Section: Framework For Habitat Comparisonmentioning
confidence: 99%
See 1 more Smart Citation